Bridging information requirements and information needs assessment: do scenarios and vignettes provide a link? - Christine Urquhart (Information Research: An International Electronic Journal)
The aim of the paper is to compare the philosophies of the vignette and critical incident techniques in information behaviour research, with the methodologies used in object oriented analysis such as use case scenarios and CRC (class, responsibility, collaboration) cards. The principles of object oriented analysis are outlined, noting the emphasis on obtaining the "storyline" or "scripts" for information requirements analysis through use cases and CRC cards.  The critical incident technique and vignettes are used to obtain valid interpretations of users" information behaviour, using a storyline approach for data collection (and analysis) which is similar to that of object oriented analysis. Some examples illustrate how techniques developed in object oriented analysis could be used for data display in information behaviour studies. Concludes that the methods developed by software engineering could be adapted usefully for information behaviour research.